2018
DOI: 10.1111/imre.12287
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction of Cross-Border Marriage Migrants in South Korea: Exploring the Social Network Effects

Abstract: This study examines the recent phenomenon of “cross-border marriage” in South Korea: foreign brides migrating into Korea to get married to Korean bachelors. Using data from the National Survey of Multicultural Families 2009, one of the biggest data sets on marriage migrants, we analyze how the difference in migrants’ initial methods of entry affects the level of their life satisfaction. The findings show greater life satisfaction for those who used personal social networks, when compared with those who used co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Studies also described other immigration policies and restrictions on citizenship rights such as right to residency status by country, Taiwan imposed 3 years of immigration restriction, United Kingdom 1 year, China 5 years, Korea 7 years upon being granted conditional residency status (Williams & yu, 2006; Yu & Chen, 2018); dependence status where a qualitative finding revealed that men use deportation as a threat to the woman and her children to cage her and make her more vulnerable to domestic violence (Raj et al, 2019; Raj & Silverman, 2002; Tang & Wang, 2014); immigration flows restrictions (Carver, 2016); minimum available amount in a bank account to obtain a dependent status; in America, a K–1 or fiancée visa is issued with the condition that the couple marries within 90 days (US Dept. of Homeland Security, 2017); citizenship after 3 years of residence for those married to American citizens and 5 years for those married to Americans holding legal permanent residency (de Hart, 2017; Stamper Balistreri et al, 2017) and policies of probationary visa all renders women prone to domestic violence in their marital homes (Akyuz & Tursun, 2019; Anitha, 2019; Anitha et al, 2018; Kim, 2010, 2014; Kudo, 2017; Qureshi, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Studies also described other immigration policies and restrictions on citizenship rights such as right to residency status by country, Taiwan imposed 3 years of immigration restriction, United Kingdom 1 year, China 5 years, Korea 7 years upon being granted conditional residency status (Williams & yu, 2006; Yu & Chen, 2018); dependence status where a qualitative finding revealed that men use deportation as a threat to the woman and her children to cage her and make her more vulnerable to domestic violence (Raj et al, 2019; Raj & Silverman, 2002; Tang & Wang, 2014); immigration flows restrictions (Carver, 2016); minimum available amount in a bank account to obtain a dependent status; in America, a K–1 or fiancée visa is issued with the condition that the couple marries within 90 days (US Dept. of Homeland Security, 2017); citizenship after 3 years of residence for those married to American citizens and 5 years for those married to Americans holding legal permanent residency (de Hart, 2017; Stamper Balistreri et al, 2017) and policies of probationary visa all renders women prone to domestic violence in their marital homes (Akyuz & Tursun, 2019; Anitha, 2019; Anitha et al, 2018; Kim, 2010, 2014; Kudo, 2017; Qureshi, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…These immigrant women are both unable to report or escape domestic violence due to lack of money and their illegal status. As such, women continue to endure all sorts of maltreatment and inhuman treatments from both, their arranged husbands and the brokers to whom they would turn to for help (Yu & Chen, 2018).…”
Section: Domestic Violencementioning
confidence: 99%
“…Since 2003, around 10% of marriages in Korea have been categorized as "cross-border," with the majority formed through marriage migration and concentrated in low-income households (Ministry of Gender Equality and Family 2016). Today, the image of "mail-order-brides" and wives being commercially bought continues, despite evidence demonstrating the predominant use of social networks over commercial brokering services (Yu and Chen 2018) and the erroneous conception of marriage migrants as lacking agency (Constable 2005).…”
Section: Context the Korean Family And Marriage Migrationmentioning
confidence: 99%